Chronic constipation as a risk factor of urinary tract infection in children - Irna Fajri Syahny; Mohammad Juffrie; Pungky Ardany Kusuma (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
The prevalence of urinary tract infection (UTI) in children is still quite high. In Dr. SardjitoGeneral Hospital, Yogyakarta the incidence of UTI is reported about 3.5%. One of the riskfactors of the incidence of UTI is chronic constipation. However, it is often not a concern in themanagement of UTI pediatric patients. The aim of the study was to evaluate the influence ofchronic constipation in increasing the risk of UTI in children. This was an observational studywith case-control design. Children with symptoms of UTI who visited at the Installation of ChildHealth, Dr. Sardjito General Hospital, Yogyakarta underwent dipstick urinalysis test and urineculture examination. Patients who showed positive urine culture was included in the case group,meanwhile patients who showed negative urine culture was included in the control group. Allpatients were then asked the history of the chronic constipation. The association between theconstipation and the incident of UTI was evaluated using bivariate analysis continued bymultivariate analysis. One hundred and twenty eight eligible subjects consisting 64 subjects ineach group were involved in this study. Statistical analysis showed that children with chronicconstipation have a 3.77 times higher risk of UTI (OR=3.77; 95%CI=3.21-4.32) compare tothose without constipation. Furthermore, the chronic constipation remained to be independentrisk factor of UTI. The incidence of UTI increased 3.99 times higher in children with constipationcompare to those without constipation (aOR=3.99; 95% CI=1.028-15.48). In conclusion, chronicconstipation has been proven to be a risk factor of UTI in children